ROLE OF AMH, FSH, ANDROGEN AND ESTRADIOL AS MARKER OF PCOS FOLLICULOGENESIS: NARATIVE REVIEW - Erna Yovi Kurniawati; Noor Pramono (An-Najat, 2025)
Polycystic Ovary Syndrome (PCOS) poses a significant challenge in reproductive medicine due to its complex aetiology involving hormonal dysregulation, metabolic perturbations, and genetic predispositions. Central to PCOS pathogenesis is the disruption of folliculogenesis, the process vital for female reproductive health, characterized by the formation of numerous small antral follicles that fail to mature properly. This narrative review explores the roles of Anti-Müllerian Hormone (AMH), Follicle-Stimulating Hormone (FSH), androgens, and oestradiol as markers of PCOS folliculogenesis. AMH, prominently produced by granulosa cells, exhibits elevated levels in PCOS, contributing to excessive follicular recruitment and persistence. Dysregulation of FSH, androgen, and oestradiol further complicates follicular development, exacerbating PCOS-related abnormalities. Understanding the interplay between these markers is crucial for diagnosing and managing PCOS. However, challenges persist, including the lack of standardized serum AMH thresholds and technical limitations in testing methodologies. Further research is warranted to establish these thresholds and refine diagnostic approaches. Moreover, insights into hormonal mechanisms in PCOS folliculogenesis hold promise for developing targeted therapies to alleviate its impact on reproductive health.